Analisis Implementasi Bauran Pemasaran Studi pada Konsumen Kartika Snack Lumajang - Dina Marta Suraidah Fatma (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to explore the application of the 4Cs marketing mix (Customer, Cost, Convenience, Communication) at Kartika Snack in Lumajang, which is well known as a producer of kepok banana chips. Using a qualitative approach and descriptive method, data was collected through observation, interviews with the owner and customers, and documentation. The findings showed that Kartika Snack successfully implemented an effective marketing strategy by emphasizing understanding of customer needs, competitive pricing, friendly service, and responsive communication. The price and convenience components are proven to have a major influence on customer satisfaction and loyalty. This study recommends that Kartika Snack continue to evaluate marketing strategies and expand the reach of online marketing to improve brand image and market share. The results of this study are expected to be a reference for the development of marketing strategies in the food sector in Indonesia
Reaploud Repository February_Hasyim
Keywords: Marketing Mix; Marketing Strategy